Clinical outcome of patients with the Brugada type 1 electrocardiogram without prophylactic implantable cardioverter defibrillator in primary prevention: a cumulative analysis of seven large prospective studies. Issue Volume 20:Issue FI 1(2018) (3rd October 2017) - Delise, Pietro; Probst, Vincent; Allocca, Giuseppe; Sitta, Nadir; Sciarra, Luigi; Brugada, Josep; Kamakura, Shiro; Takagi, Masahiko; Giustetto, Carla; Calo, Leonardo
Abstract: Aims: Patients with the Brugada type 1 ECG (Br type 1) without previous aborted sudden death (aSD) who do not have a prophylactic ICD constitute a very large population whose outcome is little known. The objective of this study was to evaluate the risk of SD or aborted SD (aSD) in these patients. Methods and results: We conducted a meta-analysis and cumulative analysis of seven large prospective studies involving 1568 patients who had not received a prophylactic ICD in primary prevention. Patients proved to be heterogeneous. Many were theoretically at low risk, in that they had a drug-induced Br type 1 (48%) and/or were asymptomatic (87%), Others, in contrast, had one or more risk factors. During a mean/median follow-up ranging from 30 to 48 months, 23 patients suffered SD and 1 had aSD. The annual incidence of SD/aSD was 0.5% in the total population, 0.9% in patients with spontaneous Br type 1 and 0.08% in those with drug-induced Br type 1 ( P  = 0.0001). The paper by Brugada et al. reported an incidence of SD more than six times higher than the other studies, probably as a result of selection bias. On excluding this paper, the annual incidence of SD/aSD in the remaining 1198 patients fell to 0.22% in the total population and to 0.38 and 0.06% in spontaneous and drug-induced Br type 1, respectively. Of the 24 patients with SD/aSD, 96% were males, the mean age was 39 ± 15 years, 92% had spontaneous Br type 1, 61% had familial SD (f-SD), and only 18.2% had a previous syncope; 43% had a positive electrophysiological study. Multiple meta-analysis of individual trials showed that spontaneous Br type 1, f-SD, and previous syncope increased the risk of SD/aSD (RR 2.83, 2.49, and 3.03, respectively). However, each of these three risk factors had a very low positive predictive value (PPV) (1.9–3.3%), while negative predictive values (NPV) were high (98.5–99.7%). The incidence of SD/aSD was only slightly higher in patients with syncope than in asymptomatic patients (2% vs. 1.5%, P  = 0.6124). Patients with SD/aSD when compared with the others had a mean of 1.74 vs. 0.95 risk factors ( P  = 0.026). Conclusion: (i) In patients with Br type 1 ECG without an ICD in primary prevention, the risk of SD/aSD is low, particularly in those with drug-induced Br type 1; (ii) spontaneous Br type 1, f-SD, and syncope increase the risk. However, each of these risk factors individually has limited clinical usefulness, owing to their very low PPV; (iii) patients at highest risk are those with more than one risk factor.